Streptococcus pneumoniae Capsule Biosynthesis Protein CpsB Is a Novel Manganese-Dependent Phosphotyrosine-Protein Phosphatase - Morona, Judy K. (American Society for Microbiology, 2002)
The first four genes of the capsule locus (cps) of Streptococcus pneumoniae (cpsA to cpsD) are common to most serotypes. We have previously determined that CpsD is an autophosphorylating protein-tyrosine kinase, demonstrated that CpsC is required for CpsD tyrosine-phosphorylation, and shown that CpsB is required for dephosphorylation of CpsD. In the present study we show that CpsB is a novel manganese-dependent phosphotyrosine-protein phosphatase that belongs to the PHP (polymerase and histidinol phosphatase) family of phosphoesterases. We also show that an S. pneumoniae strain with point mutations in cpsB, affecting one of the conserved motifs of CpsB, is unencapsulated and appears to be morphologically identical to a strain in which the cpsB gene had been deleted.